2021
DOI: 10.1007/s00228-021-03210-0
|View full text |Cite
|
Sign up to set email alerts
|

Low- vs high-dose ARNI effects on clinical status, exercise performance and cardiac function in real-life HFrEF patients

Abstract: Purpose Only a few studies are available on dose-related effects of sacubitril/valsartan (angiotensin receptor neprilysin inhibition (ARNI)) in real-life patients with heart failure and reduced ejection fraction (HFrEF). We sought to investigate clinical and functional effects in real-life HFrEF patients receiving ARNI at a different cumulative dose. Methods This was an observational study in consecutive outpatients admitted for HFrEF from October 2017 to June 2019. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 34 publications
4
14
0
Order By: Relevance
“…Another study found that patients who were receiving ARNI doses equal to or exceeding 72/78 mg/day had better functional capacity, as determined by the 6MWT and KCCQ, when compared with patients who received lower doses of ARNI. Importantly, in this study, patients with lower ARNI doses also demonstrated improved functional capacity during the follow-up period 29 . Our study aligns with both of these studies regarding the time frame for improved activity, as we also observed improvement as early as 3–6 months after ARNI initiation.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Another study found that patients who were receiving ARNI doses equal to or exceeding 72/78 mg/day had better functional capacity, as determined by the 6MWT and KCCQ, when compared with patients who received lower doses of ARNI. Importantly, in this study, patients with lower ARNI doses also demonstrated improved functional capacity during the follow-up period 29 . Our study aligns with both of these studies regarding the time frame for improved activity, as we also observed improvement as early as 3–6 months after ARNI initiation.…”
Section: Discussionsupporting
confidence: 90%
“…Previous research has indicated that ARNI treatment can improve functional capacity in patients with HFrEF. Most of these studies focused mainly on patients who were administered high-dose ARNI 9,28,29 . For instance, a study by Malfatto et al 28 showed an improvement in CPET parameters in patients who were administered with an average dose of 318 mg/day of ARNI after 6 months of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that high-dose sacubitril/valsartan can not only improve clinical status, exercise performance, and cardiac function, but also result in a lower mortality or hospitalization rate for HFrEF patients as compared to low-dose therapy [21,22]. As a consequence, our heart failure team developed a rigorous follow-up plan that focused on titrating sacubitril/valsartan to achieve the target dose for HF patients.…”
Section: Discussionmentioning
confidence: 99%